Photobiomodulation in Alzheimer’s Disease—A Complementary Method to State-of-the-Art Pharmaceutical Formulations and Nanomedicine? - Laura Marinela Ailioaie; Constantin Ailioaie; Gerhard Litscher (2023)
Alzheimer’s disease (AD), as a neurodegenerative disorder, usually develops slowly but gradually worsens. It accounts for approximately 70% of dementia cases worldwide, and is recognized by WHO as a public health priority. Being a multifactorial disease, the origins of AD are not satisfactorily understood. Despite huge medical expenditures and attempts to discover new pharmaceuticals or nanomedicines in recent years, there is no cure for AD and not many successful treatments are available. The current review supports introspection on the latest scientific results from the specialized literature regarding the molecular and cellular mechanisms of brain photobiomodulation, as a complementary method with implications in AD. State-of-the-art pharmaceutical formulations, development of new nanoscale materials, bionanoformulations in current applications and perspectives in AD are highlighted. Another goal of this review was to discover and to speed transition to completely new paradigms for the multi-target management of AD, to facilitate brain remodeling through new therapeutic models and high-tech medical applications with light or lasers in the integrative nanomedicine of the future. In conclusion, new insights from this interdisciplinary approach, including the latest results from photobiomodulation (PBM) applied in human clinical trials, combined with the latest nanoscale drug delivery systems to easily overcome protective brain barriers, could open new avenues to rejuvenate our central nervous system, the most fascinating and complex organ. Picosecond transcranial laser stimulation could be successfully used to cross the blood-brain barrier together with the latest nanotechnologies, nanomedicines and drug delivery systems in AD therapy. Original, smart and targeted multifunctional solutions and new nanodrugs may soon be developed to treat AD.